2014
DOI: 10.1016/j.jtcvs.2014.02.066
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid versus Norwood procedure for hypoplastic left heart syndrome: Contemporary series from a single center

Abstract: In our review, we found no statistically significant difference in survival or resource usage between those patients undergoing the Norwood procedure and those undergoing a hybrid procedure as initial palliation for hypoplastic left heart syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 17 publications
3
28
0
1
Order By: Relevance
“…Retrospective review of our patient cohort shows that some of the earlier cohort who underwent venous shunt pathway may have been assigned an arterial shunt in the current era (1 early mortality in the venous group, who had a restrictive septum). Our mortality results are still comparable to most of the reported series, 13,14 bearing in mind that in our center, the hybrid procedure is reserved for higher-risk, more complex, and unstable patients in whom a Norwood procedure would carry an unacceptable high risk. A previous report from our center has confirmed the higher risk of our hybrid cases using a modified comprehensive Aristotle score.…”
Section: Discussionsupporting
confidence: 81%
“…Retrospective review of our patient cohort shows that some of the earlier cohort who underwent venous shunt pathway may have been assigned an arterial shunt in the current era (1 early mortality in the venous group, who had a restrictive septum). Our mortality results are still comparable to most of the reported series, 13,14 bearing in mind that in our center, the hybrid procedure is reserved for higher-risk, more complex, and unstable patients in whom a Norwood procedure would carry an unacceptable high risk. A previous report from our center has confirmed the higher risk of our hybrid cases using a modified comprehensive Aristotle score.…”
Section: Discussionsupporting
confidence: 81%
“…Follow-up studies have failed to reveal a significant difference in survival with regard to palliation strategy 1 year after stage I [66,67]. This has been confirmed, with more recent results showing equivalent 1-year survival in both groups [48,61,75]. However, the Giessen group reported outstanding results after hybrid palliation, with survival of 84% at 1 year, 78% at 2 years, 77.8% at 10 years, and 77% at 15 years [13,51].…”
Section: Survivalmentioning
confidence: 91%
“…Although some centers report laudable outcomes for the hybrid approach, others report intermediate-term outcome (mortality) no better than that of the conventional staged palliation. [1][2][3][4][5] One study found no difference in neurodevelopmental outcome at 1 year between patients managed with the conventional approach and those managed with the hybrid approach. 6 Although the first stage of the hybrid approach avoids a prolonged operation with cardiopulmonary bypass, deep hypothermia, and circulatory arrest, these techniques are typically required at the time of the ''comprehensive stage II'' operation.…”
Section: See Editorial Commentary Page 1101mentioning
confidence: 99%